Analysing Instructional Videos on Arithmetic Operations on Fractions in Elementary School Students - Anisa Hayatul Milah; Karlimah Karlimah (Indonesian Journal of Primary Education, 2021)
This research was conducted based on the rapidly advancing technology and the importance of using instructional media to stimulate students' understanding. This study aims to analyze the instructional videos for fifth grade Elementary School. The method used in this research was qualitative descriptive. The data studied were instructional  videos about fractional arithmetic operations that were available on the YouTube and ruangguru applications. The data were analyzed based on the characteristics of the audio-visual instructional media, including: 1) Video clarity; 2) Stand-alone aspect; 3) User friendly; 4) Content representation; 5) Visualization with media; 6) Using high resolution quality and 7) Can be used individually or classically. The results of this study indicated that: The content of each video was quite easy to understand and remember. Videos must be accompanied by worksheets so that students take an active role, not just watching. The language used in each video was simple, easy to understand and used common language. The material presented was quite representative and the video contained stimulation regarding arithmetic operations on fractional numbers. The material contained in the video was equipped with the voice of the presenter which was quite clear and there was also text on the video, but there was no animation. Each video used a resolution high enough to produce a clear image and this video could be used on any computer. Videos can be used individually or classically and videos can be viewed anywhere and anytime. Thus, it can be concluded that the five learning videos have almost fulfilled the characteristics of audio-visual instructional media, it's just that additional animations and worksheets are needed so that the videos can be more interesting and students can play an active role.